Victimization of Queer Individual as Portrayed in Adam Silvera's More Happy Than Not Novel - Yunita, Ira Alifia; Kuncara, Singgih Daru; Ariani, Setya (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This research aims to analyze the formation of homosexual identity in an individual, the types of victimization and abuse towards queer people, as well as the effects of victimization. The researcher used Foucault’s queer theory as a main theory for this study. The data used in this research were paragraphs, sentences, dialogues and narrations. The novel entitled More Happy Than Not, which was written by Adam Silvera in 2015, was used as the source of data for this research. The results from this study showed that the character Aaron Soto went through a rather difficult progress of homosexual identity formation, which he went back and forth between identity confusion and identity assumption phases. Aaron experienced several kinds of victimization, which include physical abuse, verbal abuse, and victimization in family settings. The abuse caused Aaron to experience physical injury, self blame, as well as feelings of internalized homophobia. The homosexual identity formation, victimization and the effects of victimization are related in a sense that they work like a cycle, and the three of them worked as a cause and effect.